Enhanced DNA sequencing by hybridization. - Broude, N E (1994)
An enhanced version of DNA sequencing by hybridization (SBH), termed positional SBH (PSBH), has been developed. PSBH uses duplex probes containing single-stranded 3' overhangs, instead of simple single-stranded probes. Stacking interactions between the duplex probe and a single-stranded target should provide enhanced stringency in distinguishing perfectly matched 3' sequences. A second enhancement is the use of enzyme-catalyzed steps, instead of pure physical hybridization. The feasibility of this scheme has been investigated using biotinylated duplex probes containing single-stranded 5-base 3' overhangs, immobilized on streptavidin-coated magnetic beads. Ligation of a single-stranded target, hybridized to the single-stranded region of the duplex probes, provided enhanced discrimination of perfectly matched targets from those containing mismatches. In distinction to the serious complications caused by base composition effects in ordinary SBH, there was little effect of base composition in PSBH. The hardest mismatch to discriminate was the one furthest from the phosphodiester bond formed by ligation. However, mismatches in this position were efficiently discriminated by 3' extension of the duplex probe using a template-dependent DNA polymerase. These results demonstrate that PSBH offers considerable promise to facilitate actual implementations of SBH.